2014
DOI: 10.1103/physreve.90.022501
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric, electro-optical, and photoluminescence characteristics of ferroelectric liquid crystals on a graphene-coated indium tin oxide substrate

Abstract: Multilayer graphene was deposited on indium tin oxide (ITO) -coated glass plates and characterized by suitable techniques. A liquid crystal sample cell was designed using graphene deposited ITO glass plates without any additional treatment for alignment. Ferroelectric liquid crystal (FLC) material was filled in the sample cell. The effect of multilayer graphene on the characteristics of FLC material was investigated. The extremely high relative permittivity of pristine graphene and charge transfer between grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The detailed experimental information regarding dielectric and electro-optical measurements has already been reported in Ref. [11,[18][19][20] and references therein. All the dielectric and E-O measurements have been conducted on planar anchored sample cells.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed experimental information regarding dielectric and electro-optical measurements has already been reported in Ref. [11,[18][19][20] and references therein. All the dielectric and E-O measurements have been conducted on planar anchored sample cells.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 provides a short summary of the reported effects. As can be seen, both decrease [118,119,[121][122][123][124][125][126][127][143][144][145][146][147][148][149][150][151][152] and increase [105,120,[128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][150][151][152][153] in the electrical conductivity of liquid crystals doped with carbon-based nanomaterials were reported.…”
Section: Carbon-based Nano-objects In Liquid Crystalsmentioning
confidence: 99%
“…The electrical properties of liquid crystals doped with graphene were reported in [121][122][123][124][125][126]. According to [121], graphene sheets, implemented in the design of ferroelectric liquid crystal cell as alignment layers, reduce the electrical conductivity by a factor of ~10.…”
Section: Carbon-based Nano-objects In Liquid Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, graphene also helps in better adsorption of biomolecules due to π −π stacking, thereby improving a systems affinity to such molecules. Also, it has been reported that graphene can be deposited over ITO [17]. These hitherto mentioned ideas motivate us to propose a D-shaped single mode optical fiber sensor.…”
mentioning
confidence: 99%